Content and geographical distribution of organic carbon in soils of Uruguay - Durán, A. (Agrociencia Uruguay, 1998)
In recent years an increasing interest is observed concerning the organic carbon content of the soils because these can be either a sink or a source of some greenhouse gases, particularly carbon dioxide and so they contribute to the increase or decrease of such gases in the atmosphere and consequently influence on its temperature. Soil organic matter conservation has therefore become an objective aiming to both: (1) contribute to conservation of good physical, chemical and biological soils properties to ensure crops and pasture production levels compatible with human needs and support the sustainability of farming systems, and (2) mitigate the emission of gases which contribute to the warming of the atmosphere and so influence on global change. A basic element needed for a rational management of soil organic matter with environmental purposes is the availability of the best possible inventories of the organic carbon content of different soils and its distribution in depth through the soil profile. In this paper a first contribution to the knowledge of the global organic carbon content of the soils of Uruguay is presented from two different points of view. o one hand, estimates of that parameter are presented for deep soils, suitable for common crops, such as brunosoles (Udolls), Vertisoles, Argisoles (Udolls, Udalfs), Planosoles (Albolls and Aqualfs), Luvisoles (Udalfs p.p) and Acrisoles (Udults), discussing the carbon content to a depth of one meter and in the upper 20 and 50 centimeters of the profile in each Great Group (or Order). On the other hand, the organic carbon content of each of the soil mapping units of the Reconnaissance Soil Map of Uruguay is estimated and from the information supplied by the map, a first approximation to an estimate of the carbon content for the whole of the soils in the country is presented. The procedure followed for the computations of soil organic carbon is the same used by different authors working in similar estimates for geographical areas of variable extent and contributes to carbon data bases existing in different research institutions with both productive and environmental objectives.